Analisis Pengelolaan Keuangan Perspektif Islam UMKM (Studi Kasus UD. KERIPIK DR) - Wulan Indah Sari (Universitas Muhammadiyah Sumatera Utara, 2022)
MSMEs are one of the main driving factors for the Indonesian economy. Currently, the obstacles faced by MSMEs are: the number of MSMEs that open businesses with similar products. This study aims to analyze the financial statements applied to SMEs in an Islamic perspective. So that it can grow and be in line with the business. The method used is a qualitative descriptive method at UD.Keripik DR, which is located at Limau Manis Village, Tanjung Morawa District, Deli Serdang Regency, which is a type of trading industry with the criteria that it is still active and willing to conduct interviews about its business. The results of this study are in accordance with 4 indicators in financial management which show that SMEs can be assessed using 1) planning in the use of the budget, 2) making simple records 3) Reporting and 4) using adequate controls. However, not all MSMEs understand the reporting indicators in business financial reports.